Design of e-books: readers’ expectations in a comparative perspective (Libellarium: journal for research in the field of information and related sciences, 2014)
The aim of the paper is to compare graphic elements used for the design of printed and electronic books. The paper focuses on four main graphic elements: book cover, typography, colour and image. Ten books published in printed and electronic form in Croatia between 2010 and 2012 were used as a research sample. The research methods used are visual content analysis and interviews. The research results indicate that e-books imitate the graphic design of a printed book in many aspects. The graphic elements of an e-book highly depend on the features of e-formats and on e-readers. The main advantages of an e-book are that they are searchable, adaptable, easily linked to other digital documents, transportable, easily accessible and durable. Still, in the second phase of the research, the majority of the interviewed participants stated that reading of an e-book was something new to them. They prefer the interaction with a printed book and its visual appearance.
Keywords: graphic design; p-book; e-book; e-readers; e-book formats